2018
DOI: 10.1016/j.ymthe.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PFAR Promotes Lung Fibroblast Activation and Fibrosis by Targeting miR-138 to Regulate the YAP1-Twist Axis

Abstract: Long non-coding RNAs (lncRNAs) have been reported to be involved in various pathophysiological processes in many diseases. However, the role and mechanism of lncRNAs in idiopathic pulmonary fibrosis (IPF) have not been explicitly delineated. In the present study, we reported that lncRNA NONMMUT065582, designated pulmonary fibrosis-associated RNA (PFAR), is upregulated in the lungs of mice with lung fibrosis as well as in fibrotic lung fibroblasts. Overexpression of PFAR promoted fibrogenesis through modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…Previous studies revealed that lncRNAs participate in various cellular processes and that the dysregulation of lncRNAs usually leads to the o development of diseases, such as cancer [14] and cardiovascular diseases [15]. Moreover, several studies indicated that certain lncRNAs, such as PFAR [16], lncITPF [17], PFRL [18] and PFAL [19], act as important regulators in the progression of IPF. However, the exact functions of lncRNAs in IPF remain elusive.…”
mentioning
confidence: 99%
“…Previous studies revealed that lncRNAs participate in various cellular processes and that the dysregulation of lncRNAs usually leads to the o development of diseases, such as cancer [14] and cardiovascular diseases [15]. Moreover, several studies indicated that certain lncRNAs, such as PFAR [16], lncITPF [17], PFRL [18] and PFAL [19], act as important regulators in the progression of IPF. However, the exact functions of lncRNAs in IPF remain elusive.…”
mentioning
confidence: 99%
“…Previous studies have suggested that miRNAs were associated with the pathogenesis of cancer (20)(21)(22)(23)(24)(25). MiRNAs are promising oncogenic factor or tumor suppressors; they function as essential regulators of gene expression and are putative targets of circRNAs (19)(20)(21)(22)(23)(24). For instance, miR-93 is able to enhance the proliferation of glioma cells by targeting phosphatidylinositol 3 kinase/protein kinase B pathway (22).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are non-coding RNAs with the length of ~ 22 nt, which are potential downstream targets of other non-coding RNAs including lncRNAs and circRNAs (19,20). Previous reports have suggested that miRNAs exert their functions via binding to the 3' untranslated region of corresponding mRNAs (21,22).…”
mentioning
confidence: 99%
“…Interestingly, the expression of lncRNA NONMMUT065582, also known as pulmonary fibrosis-associated RNA (PFAR), was found to be elevated in the fibrotic lungs of mice as well as mouse fibroblasts [138]. The LncRNA, PFAR, was shown to promote the development of fibrosis by acting as ceRNA for miR-138 and regulating the expression of yes-associated protein 1 (YAP1).…”
Section: Lon Non-coding Rna Nonmmut065582 (Pfar)mentioning
confidence: 99%